Analisis Pengaruh Kinerja Lalu Lintas Terhadap Biaya Operasional Kendaraan Menggunakan Metode MKJI 1997 - Shahnarani Ivanov Putrinur; Muhammad Oka Mahendra (Jurnal Konstruksi, 2025)
Anyer-Cilegon National Road is a vital section that experiences high density due to vehicle activity that often stops on the road, triggered by the use of sidewalks and shoulders as parking areas and street vendors' sales locations. This study adopts a quantitative approach through direct field surveys to collect primary data related to road capacity, traffic volume, side obstacles, vehicle speed, and vehicle operating costs (VOC) by referring to the 1997 MKJI method. The results of this study aim to analyze the effect of traffic performance on vehicle operating costs using the 1997 MKJI method. The results show that the level of road service is in the C-D category, with the implementation of alternative solutions successfully reducing operational costs by IDR 7.9 million. Although this reduction is not significant in nominal terms, the strategy is effective in minimizing fuel waste and spare part costs, reflecting the optimization of operational efficiency. These findings underline the importance of traffic management interventions, such as relocation of illegal parking activities and regulation of street vendors, to improve road service levels. Further research is recommended to explore the integration of smart parking technology and widening of traffic space to address the root causes of congestion in this strategic corridor.